2011
DOI: 10.1007/s11606-011-1703-z
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Between Electronic Health Records: Effects on Ambulatory Prescribing Safety

Abstract: BACKGROUND: Healthcare providers previously using older electronic health records (EHRs) with electronic prescribing (e-prescribing) are transitioning to newer systems to be eligible for federal meaningful use incentives. Little is known about the safety effects of transitioning between systems. OBJECTIVE: To assess the effect of transitioning between EHR systems on rates and types of prescribing errors, as well as provider perceptions about the effect on prescribing safety. DESIGN, PARTICIPANTS: Prospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…3,4 Despite these potential benefits, there are a number of pitfalls in switching to electronically-submitted prescriptions. Errors, such as those arising from prescriber omissions or input errors, may require clarification by pharmacy staff (including avoidable calls to prescriber offices) in order to correct legal, technical, or clinical deficiencies.…”
Section: ■■ Electronic Prescription Errors In An Ambulatory Pharmacymentioning
confidence: 99%
“…3,4 Despite these potential benefits, there are a number of pitfalls in switching to electronically-submitted prescriptions. Errors, such as those arising from prescriber omissions or input errors, may require clarification by pharmacy staff (including avoidable calls to prescriber offices) in order to correct legal, technical, or clinical deficiencies.…”
Section: ■■ Electronic Prescription Errors In An Ambulatory Pharmacymentioning
confidence: 99%
“…Alert fatigue has been well documented and may help account for the mixed safety benefits seen among ambulatory e-prescribing systems [2, [6][7][8][9]11,12]. Indeed, in a companion quantitative study we conducted among the same group of providers, we found that overall prescribing error rates were higher pre-transition than post-transition; however, improvements in safety were mainly caused by reducing only one specific type of error -inappropriate abbreviation errors [34].…”
Section: Discussionmentioning
confidence: 94%
“…We accomplished triangulation by comparing results across semi-structured interviews, field observations, and a brief, de-identified provider survey that assessed their experiences using the two systems. The survey results are reported elsewhere [34].…”
Section: Discussionmentioning
confidence: 99%
“…3 Adoption of the modernized EHRS has been extremely slow despite the potential financial incentives in utilizing systems that fulfill the definition of meaningful use as outlined in the HITECH Act. 4 In a recent survey, Jha et al 5 found that Ͼ 75% of hospitals reported adoption of electronic laboratory and radiologic reporting systems. Our institution adopted an electronic laboratory reporting system in the early 1990s.…”
Section: Discussionmentioning
confidence: 99%